Age-dependent decline in Kv4 channels, underlying molecular mechanisms, and potential consequences for coordinated motor function - Vallejos, Maximiliano Jose, author; Tsunoda, Susan, advisor; Amberg, Gregory C., committee member; Bouma, Gerrit, committee member; Mykles, Donald, committee member; Tamkun, Michael, committee member (Colorado State University. Libraries, 2019)
The voltage-gated potassium channel, Kv4, is widely expressed in the central nervous system and it is responsible for a highly conserved rapidly inactivating A-type K+ current. Kv4 channels play a role in the regulation of membrane excitability, contributing to learning/memory and coordinated motor function. Indeed, recent genetic and electrophysiological studies in Drosophila have linked Kv4 A-type currents to repetitive rhythmic behaviors. Because a deterioration in locomotor performance is a hallmark of aging in all organisms, we were interested in examining the effects of age on Kv4/Shal channel protein. In this dissertation, I use Drosophila as a model organism to characterize an age-dependent decline in Kv4/Shal protein levels that contributes to the decline in coordinated motor performance in aging flies. Our findings suggest that accumulation of hydrogen peroxide (H2O2) is amongst the molecular mechanisms that contribute to the age-dependent decline of Kv4/Shal. We show that an acute in vivo H2O2 exposure to young flies leads to a decline of Kv4/Shal protein levels, and that expression of Catalase in older flies results in an increase in levels of Kv4/Shal and improved locomotor performance. We also found that the scaffolding protein SIDL plays a role in maintaining Kv4/Shal protein levels and that SIDL mRNA declines with age, suggesting that an age-dependent loss of SIDL may also lead to Kv4/Shal loss. In behavioral studies, we found that a knockdown of SIDL resulted in a lethal phenotype, leading to a large decline in Drosophila eclosion rates, an event that requires coordinated peristaltic motions. Expression of SIDL or Kv4/Shal in this SIDL knockdown genetic background resulted in a partial rescue; these results are consistent with a model in which SIDL and Kv4/Shal play a role in coordinated peristaltic motions and are required for successful eclosion. The results presented in this dissertation provide new insight into the possible molecular mechanisms that underlie an age-dependent decline in Kv4/Shal protein. We identify two contributing factors: 1) ROS accumulation, and 2) the interacting protein SIDL. Our data also suggests that this age-dependent decline in Kv4/Shal levels is likely to be conserved across species, at least in some brain regions. Because Kv4/Shal channels have been implicated in the regulation of long-term potentiation and in repetitive rhythmic behaviors, the loss of Kv4/Shal may contribute to the age-related decline in learning/memory and motor function.
Keywords: Kv4; voltage-gated; ion channels; aging; potassium channels; Drosophila